Binding specificity of antiidiotypic autoantibodies to anti-DNA antibodies in humans. - Sasaki, T (1988)
Human antiidiotypic antibodies to anti-DNA antibodies can be separated into at least two categories based on their binding to anti-DNA, antiidiotypic antibodies, and antigens. One type was found mainly in inactive stage of SLE. The antiidiotypic antibodies appear to be directed towards idiotype (Id) determinants in the antigen-binding sites of anti-DNA antibodies. Antibody from patient T.K. acted like a mirror image of anti-single-stranded DNA antibodies, O-81, as determined by a competitive inhibition RIA. Antibodies from patient S.U. also seemed to be Ab 2 beta and Ab 2 gamma to anti-double-stranded(ds) DNA antibodies, NE-1. Most of normal subjects, on the other hand, had antibodies that bound to the human monoclonal anti-ds DNA antibodies, NE-1, NE-13, 7F4, and O-81. The Id-anti-Id interaction was not inhibited by the addition of DNA. Thus, normal subjects had Ab2 alpha activity that recognizes Id determinants in the framework region common among anti-DNA antibodies, whereas antiidiotypic antibodies in most SLE sera appear to show Ab 2 beta and Ab 2 gamma activity. The results provide evidence that the Id network system regulates immunological tolerance to DNA in humans.